SIMULATION OF MINE FILLING MODEL THE BATU HIJAU BECOME A POST-MINING LAKE PT AMMAN MINERAL NUSA TENGGARA - Suryadi, Muhammad
The Batu Hijau mine is one of the largest copper and gold mines in Indonesia which has been in production since 2000. In accordance with the BH2014BPv2 mine-plan, it is estimated that active mining activities will end in 2027 and subsequently only process ore in the stockpile with copper content is low to moderate until early 2037. After mining activities end, a pit-hole will be formed with an average diameter of 2,749 m, a depth of 705 m (from an altitude of -390 mRL to 315 mRL) and an estimated pit-hole hole can hold 807,773,048 m3 water and will be a mine hole called a pit lake. The research aimed to determine the length of time to fill the pit lake until it reaches the runoff point at 260 mRL. This is important to know because it is closely related to operational costs after mining activities end until the mine pit water overflows into the water bodies outside the mine. The duration of filling in the pit lake is also closely related to the quality of pit lake water which will overturn, meaning that the longer the retention time of the water in the pit lake, it is expected that the water quality of the mine pit will be better. This is expected to occur more chemical reactions (metal deposition). To get the right filling duration, a filling scenario is created that is tailored to the characteristics and role of each water component that enters the mine pit. The pit lake filling simulation model uses 6 scenarios where the tailings treatment from the stockpile processing is placed at the bottom of the pit lake or continues to be streamed to the DSTP facility which has been carried out so far. The simulation results show that the time to fill the pit lake without placing the tailings takes between 45.4-51.6 years, whereas if the tailings are discharged to the bottom of the pit lake it only takes 23.3-26.3 years to reach the overflow point at 260 mRL. . The time difference between placing and not placing the tailings to the bottom of the pit was 21-25 years. It is estimated that the simulation with scenario # 2 is the best, because the tailings entering the bottom of the mine pit coincides with the flow of good quality water from the forest area and then seepage water flows over the tailings sediment once the tailings placement is complete. It is hoped that good stratification will occur due to the difference in density between clean water (forest area and rainfall), seepage water and tailings.